Nano-biomarker-Based Surface-Enhanced Raman Spectroscopy for Selective Diagnosis of Gallbladder and Liver Injury - Lee, Sanghwa; Tak, Eunyoung; Cho, Yu Jeong; Kim, Jiye; Lee, Jooyoung; Lee, Ryunjin; Lee, Kwanhee; Kwon, Minsung; Yoon, Young-In; Lee, Sung-Gyu; Namgoong, Jung-Man; Kim, Jun Ki (Biochip journal, 2022)
During living donor liver transplantation, a number of blood vessels and bile ducts are anastomosed while the liver and gallbladder are resected in the donor and recipient. Early detection and treatment of complications after surgery by evaluating the function of blood vessels and the biliary tract is crucial. A biosensing chip that can monitor patient health status from the bile excreted during the recovery process has been developed using a surface-enhanced Raman sensing chip. Surface-enhanced Raman spectroscopy signals of bile obtained from normal bile duct ligation and gallbladder damage mouse models using a cautery device were identified and analyzed. The surface-enhanced Raman chip with a nanometer-level porous structure can selectively separate the nanometer biomarkers and measure the Raman signal. Through the detection of nanometer biomarkers in the bile and comparative analysis of histopathology, the Raman signal in the damaged gallbladder was compared with that caused by liver damage due to bile duct ligation, showing that it becomes a biosensing chip for monitoring recovery.